The use of presumptions in determining liability for passive participation in price-fixing cartels: a comparative study - Preller, Surita (Department of Commercial Law, 2025)
While competition authorities worldwide share a common resolve to denounce cartels, they adopt varying approaches to their prosecution and punishment. The inherent secrecy of cartels makes it a daunting task to strike the right balance in legislative and governmental intervention. For that reason, courts in different jurisdictions have allowed evidentiary presumptions aimed at aiding authorities in establishing the essential elements of transgressions, particularly in cases of price-fixing. The appropriate balance between reliance on evidentiary presumptions and the burden of proof is of paramount significance in the context of price-fixing offences. Finding this balance is vital for preventing detrimental effects on competition and market dynamics. The issue considered herein is what the appropriate balance is for South African competition law, after considering the examples provided by the European Union (“EU”) and the United States of America (“US”) in their reliance on evidentiary presumptions. In the EU, the paramount focus lies on the competitive process. The EU has been developing their competition law jurisprudence on the use of presumptions for many years and the US is not far behind. South Africa has progressively incorporated concepts and practices from the EU system into its legal framework, exemplified by the introduction of the concept of public distancing as a rebuttal to the presumption of involvement in the EU. This thesis delves into the European and U.S. positions respectively, analysing the process of proving and defending price-fixing cases, including the development of presumptions. It explores the South African position and the interplay of systems to find that the South African context is unique due to historical complexities and aims of the South African Competition Act. The aim is to determine the extent to which foreign systems provide guidance for addressing the legal questions raised in the South African context. This thesis then suggests that the US model might offer a more balanced approach that aligns with South Africa's specific needs and circumstances and gives reasons for this. It is emphasised, however, that each legal system must be considered and understood as a whole before categorical rules are drawn and transplanted from one to the other as contextual differences are present.